INCREASING IDEOLOGICAL IMMUNITITE AMONG THE YOUNG OFFICERS - Shukhrat Ashurov (Web of Journals Publishing, 2024)
In this article it was discussed about factors that cause falling under the influence of destructive ideas and protecting young people, especially, young officers from such motives. Various opinions were analyzed and recommendations were presented.
Keywords: military personnel, destructiveness, psychology, ideological fighting, factors, personal dissonance.